Penerapan Pembelajaran Role Playing Game (RPG) dalam Materi Pengurusan Jenazah untuk Meningkatkan Hasil Belajar Siswa Kelas IX SMP Islam Roushon Fikr - Roziqin, Muhamad Khoirur; Rofiq, Ahmad Ainur (JoEMS (Journal of Education and Management Studies), 2024)
This research aims to determine the effectiveness of implementing the role playing game learning method in improving student learning outcomes in the material on adab towards corpses in class IX of Roushon Fikr Islamic Middle School. The research method used is quantitative with a pre-test and post-test design. The research population was all students in class IX of Roushon Fikr Islamic Middle School for the 2023/2024 academic year, with a sample of 28 students selected randomly. The research instrument used was multiple choice questions to measure student learning outcomes. Data were analyzed using paired t-test to compare pre-test and post-test results. The research results showed that there was a significant increase in student learning outcomes after implementing the role playing game method (p < 0.05). Thus, it can be concluded that the role playing game method is effective in improving student learning outcomes on adab towards corpses in class IX of Roushon Fikr Islamic Middle School.